2022
DOI: 10.3390/microorganisms10081581
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impacts on the Marine Cycling of Biogenic Sulfur: A Review

Abstract: A key component of the marine sulfur cycle is the climate-active gas dimethylsulfide (DMS), which is synthesized by a range of organisms from phytoplankton to corals, and accounts for up to 80% of global biogenic sulfur emissions. The DMS cycle starts with the intracellular synthesis of the non-gaseous precursor dimethylsulfoniopropionate (DMSP), which is released to the water column by various food web processes such as zooplankton grazing. This dissolved DMSP pool is rapidly turned over by microbially mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 195 publications
0
7
0
Order By: Relevance
“…However, given the order(s) of magnitude difference between the anthropogenic sulfur compound reservoirs and biogenic emissions (from landfills, swamps, and so on) in megacity environments, such contributions are expectedly negligible. Here, as in studies from similar polluted environments, , and based on the weak soil microbial activity and the low biogenic flux estimates of sulfur compounds in inland soils, , the contribution of biogenic sulfur is considered insignificant (i.e., f Bio = 0 in eq ). Secondly, it has been reported that K + accounts for a maximum of 5%, while SO 4 2– accounts for ∼1% in fresh biomass burning-derived particles from various biomes .…”
Section: Discussionmentioning
confidence: 99%
“…However, given the order(s) of magnitude difference between the anthropogenic sulfur compound reservoirs and biogenic emissions (from landfills, swamps, and so on) in megacity environments, such contributions are expectedly negligible. Here, as in studies from similar polluted environments, , and based on the weak soil microbial activity and the low biogenic flux estimates of sulfur compounds in inland soils, , the contribution of biogenic sulfur is considered insignificant (i.e., f Bio = 0 in eq ). Secondly, it has been reported that K + accounts for a maximum of 5%, while SO 4 2– accounts for ∼1% in fresh biomass burning-derived particles from various biomes .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the occurrence of such pandemics may become more frequent in the near future. 15 , 16 Thus, according to the WHO and the US CDC there are several pathogens that could cause future pandemics including Crimean-Cong haemorrhagic fever, Ebola virus disease and Marburgh virus disease, Lassa fever, Middle East respiratory syndrome (MERS), Nipah and henipaviral disease, Rift Valley fever, Zika virus, Disease X, Cholera, Polio, Enterovirus-71, high drug-resistant Tuberculosis and avian influenza H5N1. 17 , 18 For example, as this manuscript is written the avian influenza H5N1 is subject of close surveillance by the WHO and the Institute of Public Health of Chile where last March 2023 was reported a human infection of avian influenza H5N1.…”
Section: Risk Of Emerging Respiratory Infectious Disease Pandemicsmentioning
confidence: 99%
“…Many studies have focused on the temporal and spatial distributions and transformation of DMS and DMSP in the surface seawater and the sea‐to‐air exchange, as well as the effects of some environmental factors on these sulfur compounds (Jackson & Gabric, 2022; Kiene, 1992; O'Brien et al., 2022; Owen et al., 2021; Shemi et al., 2021; Yang et al., 2011; Yu et al., 2021). The Bohai Sea (BS) and Yellow Sea (YS) are marginal seas located in the western Pacific Ocean that comprise a total area of 460,000 km 2 (Chen et al., 2022).…”
Section: Introductionmentioning
confidence: 99%